Barriers to Succession Planning of Family-Owned Businesses in Abia State - Alozie, Elsie N.; Anam, Bassey E.; Oko, Blessing O. (Journal of Home Economics Research, 2024)
This paper examined barriers to succession planning of family-owned businesses in Abia state. Specifically, the study determined barriers to succession planning related to: founder, family and employees of family-owned businesses. The paper adopted survey research design. A total of 345 family-owned businesses drawn from Ariaria international market and Umuahia ultra-modern market served as the population of the study. Data were collected using questionnaire. Data were analysed using frequency counts, percentages and weighted mean. Findings show that the founder’s-related barriers to succession planning ranged from fear of death (X= 3.5), and reluctance to let go of his leadership position (X = 3.7). Family-related barrier included the family’s unwillingness to relinquish their places in the business (X = 3.6); as well as, socio-cultural challenges within the environment the business is situated. The employees’ disinclination toward formalization of the business (X = 3.4) constituted employee-related barrier. The paper therefore recommended that owners of family businesses should bring in the successor into the family business as early as possible, and also make available to the would-be successor, vital information that has been used to manage the business right from beginning of the business up to the time of the entrepreneur’s exit.